Ritual as Living Interpretation: A Phenomenological Study of Frederick M. Denny's Thought - Cahaya Khaeroni (Al Qalam, 2025)
This study explores the thought of Frederick M. Denny on Islamic rituals through a phenomenological approach. Denny critiques the neglect of performative ritual aspects in Islamic studies, especially among Muslim scholars and Orientalists. He emphasizes that rituals are not merely symbolic actions but living interpretations rooted in sacred space, time, and theological significance. Drawing on theories such as Sacred Space and Time, Topocosm, and Rites of Passage, Denny provides a comprehensive framework to understand Islamic ritual practices more deeply. His criticism of previous scholars such as Nadel and his engagement with figures like Snouck Hurgronje and Clifford Geertz highlights the importance of integrating textual sources with contextual performance in ritual analysis. This study finds that Denny’s contributions offer significant potential to bridge the gap between normative doctrine and lived religious practices in Muslim societies. His emphasis on the Qur’anic recitation and zakat as sacramental and socio-economic rituals further underlines the richness and complexity of ritual life in Islam. The study advocates for a more appreciative, critical, and scientifically grounded approach to Islamic ritual studies.